Sticky Aspirations: Organizational Time Perspective and Competitiveness - Greve, Henrich R. (Organization Science, 2002)
Managers evaluate the organizational performance by comparing it with historical aspiration levels, and are more likely to make strategic changes when the performance falls below the aspiration level. Historical aspiration levels can be updated with different speed, because a focus on current performance will lead to quickly adjusting aspiration levels where historical performance has low weight, while a focus on past performance will lead to slowly adjusting performance levels where the current performance has low weight. A simulation model of aspiration-level learning and strategic change under uncertainty yields the following findings: (1) Slow adjustments of an aspiration level gives higher performance across different levels of environmental uncertainty, (2) slow adjustments of aspirations will dominate in populations with different adjustment levels if low-performing organizations are removed and replaced by organizations of the form currently performing best, and (3) stronger selection leads to faster domination by slow adjusters. Empirical analysis of format changes in radio stations finds slow adjustment of aspiration levels to be prevalent, and finds slower adjustment in competitive markets, as predicted.